MRI in hyperacute stroke: early experience - Kamis, Mohd Fandi Al-Khafiz; Mohd Yaakob, Mohd Naim; Abdul Rahim, Ezamin; Abu Hassan, Hasyma; Yusof Khan, Abdul Hanif Khan; Azahar, Aizad; Abdul Salim, Noor Hafizah; Arshad, Nabila Hanem; Muda, Ahmad Sobri (Longe Medikal, 2023)
Background: In many institutions, computed tomography is the preferred neuroimaging modality for acute stroke (CT). MRI, on the other hand, is more sensitive in detecting infarct core. We present our early experience adopting MRI-first policy, using Putra Acute Stroke Protocol with 8-minute first 3 sequences, for hyperacute stroke. Methods: We retrospectively reviewed our early 6 months experience between June until Dec 2020. All hyperacute stroke cases who had MRI first and the door to needle (DTN) were evaluated. Results: There were total of 124 cases with 11 haemorrhagic stroke (8.9%) and 6 cases stroke mimics (4%). There were total of 105 cases of acute stroke, who had MRI first, where, 18 were thrombolysed (17.1%) while 8 cases had thrombectomy (7.6%). Fourteen were thrombolysed within 60 minutes (77.8%). DTN time range between 6 to 78 minutes with total accumulated time of 716 minutes, giving an average DTN of 42 minutes. Conclusion: Our experience shows there is no significant overall delay in DTN with higher percentage of thrombolysis rate. MRI-first policy, adopting Putra Acute Stroke Protocol, helps to achieve early and confident decision after the 8-minute scan. The stroke mimics and haemorrhagic stroke were excluded effectively. A more comprehensive study over a longer period to include other parameters might benefit the treatment decision for hyperacute stroke.